Love marriage : a novel - Ali, Monica, 1967- (Scribner, 2022)
"Yasmin Ghorami is twenty-six, in training to be a doctor (like her Indian-born father) and engaged to the charismatic, upper-class Joe Sangster, whose domineering mother, Helen, is a famous feminist. Though both Yasmin's parents and Joe's mother approve of the marriage, the cultural gulf between them is vast as, it turns out, is the gulf in sexual experience between Yasmin and Joe. The novel opens as Yasmin, her parents and her brother pile into their car, packed with Indian food prepared by Yasmin's mother, to go to dinner to meet Joe's mother in her elegant townhouse in one of London's poshest neighborhoods. Contrary to all of Yasmin's fears, her unsophisticated and somewhat flamboyant mother is embraced and celebrated by Helen and her friends. Many complications ensue when Yasmin discovers that Joe has had an affair with a co-worker, and Yasmin's ne'er do well brother is banished from the house by her father, and Yasmin's mother moves to Helen's house in protest. Love Marriage is a story of emotionally fraught self-discovery and how the secrets people keep hidden affect their most intimate relationships. Joe hides the exact nature of his promiscuous past; Yasmin's brother and mother keep a monumental secret from their father; Yasmin has a wildly erotic affair of her own; and the story of her parents' love marriage proves to be a cover-up for a dark, tragic history. In the wake of extreme upheaval, Yasmin finds herself, and her life, transformed"--